MYOPATHY AS A DESTABILIZING FACTOR OF MEAT QUALITY FORMATION - Anastasiia A. Semenova; Tatiana G. Kuznetsova; Victoria V. Nasonova; Roman V. Nekrasov; Nadezhda V. Bogolyubova (Теория и практика переработки мяса)
This review paper is devoted to myopathy of slaughter animals and poultry, and examines a relationship between fast growth of muscle tissue in hybrid pigs, broiler chickens and turkey, and high frequency of detection of spontaneous or idiopathic myopathies. The development of myopathy reduces consumer and technological properties of meat, and leads to emergence of different pathological conditions (PSE or RSE meat, «destructured meat», «white» or «green» meat, punctate hemorrhage, «wooden breast» and others). Two types of myopathic conditions are examined: myopathies caused by stress in animals and nutritional myopathies, which contribution to meat quality deterioration seems to be determinative. It is shown that the basis of the mechanism of the myopathy development is the mechanism of the successive changes in muscle tissue: damage of cell membranes and release of mitochondrial calcium, which causes hypercontraction, dystrophic changes, atrophy and necrosis of muscle fibers. To alleviate the damaging effect of two types of myopathies, different substances-adaptogens (selenium, vitamin E, flavonoids and others) can be used. It is stated that the requirements of animals in adaptogens change with an increase in the indicators of their productivity.